Foundations of modern Arab identity - Sheehi, Stephen, 1967- (University Press of Florida, 2004)
''Examines a crucial period in Arabic literature which has received insufficient attention previously--the pre-modern writers of the 19th century ... whose journalism and fiction not only shaped contemporary opinion but also subtly molded the contours and boundaries of discourse for the generations that followed.